Exercício 07.114 Apresente uma derivação à extrema direita (DED) da sentença a = b + (c * (d - e) - d) * c sobre a gramática a seguir.
G = ({A, B, C, D, E, F, G}, {a, b, c, d, e, =, +, -, *, /, (, )}, P, A)
P = {< A > -> < G > = < B >
< B > -> < D > < C > | < D >
< C > -> + < D > < C > | - < D > < C > | + < D > | - < D >
< D > -> < F > < E > | < F >
< E > -> * < F > < E > | / < F > < E > | * < F > | / < F >
< F > -> ( < B > ) | < G >
< G > -> a | b | c | d | e }
< A >
< G > = < B >
< G > = < D > < C >
< G > = < D > + < D >
< G > = < D > + < F > < E >
< G > = < D > + < F > * < F >
< G > = < D > + < F > * < G >
< G > = < D > + < F > * c
< G > = < D > + ( < B > ) * c
< G > = < D > + ( < D > < C > ) * c
< G > = < D > + ( < D > - < D > ) * c
< G > = < D > + ( < D > - < F > ) * c
< G > = < D > + ( < D > - < G > ) * c
< G > = < D > + ( < D > - d ) * c
< G > = < D > + ( < F > < E > - d ) * c
< G > = < D > + ( < F > * < F > - d ) * c
< G > = < D > + ( < F > * ( < B > ) - d ) * c
< G > = < D > + ( < F > * ( < D > < C > ) - d ) * c
< G > = < D > + ( < F > * ( < D > - < D > ) - d ) * c
< G > = < D > + ( < F > * ( < D > - < F > ) - d ) * c
< G > = < D > + ( < F > * ( < D > - < G > ) - d ) * c
< G > = < D > + ( < F > * ( < D > - e ) - d ) * c
< G > = < D > + ( < F > * ( < F > - e ) - d ) * c
< G > = < D > + ( < F > * ( < G > - e ) - d ) * c
< G > = < D > + ( < F > * ( d - e ) - d ) * c
< G > = < D > + ( < G > * ( d - e ) - d ) * c
< G > = < D > + ( c * ( d - e ) - d ) * c
< G > = < F > + ( c * ( d - e ) - d ) * c
< G > = < G > + ( c * ( d - e ) - d ) * c
< G > = b + ( c * ( d - e ) - d ) * c
a = b + ( c * ( d - e ) - d ) * c